Implementasi Sistem Pakar Mendiagnosa Penyakit Kulit Akibat Jamur Pada Manusia Berbasis Web Menggunakan Metode Forward Chaining Dan Naive Bayes - Syahbudin, Syahbudin; Rizaldy, Adhy; Rahmaniar (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2023)
In general, fungal skin disease is not a deadly disease. Most people who have been infected often leave it alone and think that the disease will heal on its own. However, if left untreated or without prompt treatment, the impact can worsen the patient's condition, one of which is permanent baldness if the fungal skin disease infects the scalp. The importance of early detection and treatment of fungal skin diseases is essential. While the current process requires a person to go to a hospital or a skin and genital specialist doctor, so they have to spend time and money to do early detection and treatment, the availability of expert doctors or experts who know a particular field is quite limited. At the same time, many patients must be diagnosed with the disease immediately and treated immediately. In a clinic, medical officers often experience difficulties when receiving patients who complain of skin diseases caused by fungi.